Humic acid resin-based amorphous porous carbon as high rate and cycle performance anode for sodium-ion batteries. (10th March 2021) - Jiang, Zhendong; Zhang, Chuanxiang; Qu, Xiaoxiao; Xing, Baolin; Huang, Guangxu; Xu, Bing; Shi, Changliang; Kang, Weiwei; Yu, Jia; Hong, Suck Won
Abstract: We developed amorphous porous carbon (i.e. humic acid resin-based amorphous porous carbon, HARC800) with the controlled porosity in the ordered structure as anode material for sodium-ion batteries (SIBs) through the optimized annealing process supported by functional lignite and sodium alginate precursors. HARC800 has well-developed interconnected mesoporous and micropores, accounting for 85.7% and 14.3%, respectively. The porous characteristic of amorphous carbon materials can curtail the diffusion path of Na +, and promote the penetration of electrolyte in the material, which is very instrumental in intensify the dynamic property of the material, thereby promoting the storage of Na + . When it is applied to the anode for SIBs, the HARC800 provides an initial reversible capacity of 260 mA h g −1 at 30 mA g −1 . Even at 2000 mA g −1, it appears 99 mA h g −1, indicating that it has excellent rate performance. It could be yielded 133 mA h g −1 after 200 cycles at 500 mA g −1, and maintain 119 mA h g −1 after 1000 cycles at 1000 mA g −1, suggesting its outstanding long-life cycle performance. This research proposes that reasonable control of the ratio of mesoporous and micropores can promote the Na + storage performance of amorphous porous carbon materials.